Avaliação do efeito biológico do extrato etanólico do fungo Trichoderma asperelloides sobre células tumorais humanas - Bárbara Gomes Kunzmann (2017)
Cancer is a multifactorial disease, with the potential to assail any individual, with no regards to social class, religion, race or place. The development of effective forms of cancer treatment, with minor side effects is of extreme relevance due to the importance of this disease in the world and its excessive cost to the public health system. Therefore, the discovery and evaluation of new therapeutic substances is highly regarded. Many of the active principles being studied today were isolated from natural resources, such as plants and microorganisms. In fact, a few of the chemotherapy drugs largely deployed in the medical facilities, like the rapamycin, are antibiotics produced by fungi or bacteria. The fungus Trichoderma asperelloides is a saprophytic, heterotrophic and cosmopolite micoparasite, related to the soil nutrient recycling and regulation that has been used as a mean of biocontrol of phytopathogens, replacing the chemical fungicides. Active principles with bactericide, antiviral, imunomodulator and antitumoral properties have already been isolated in fungi of this same genre (T. viride, T. harzianum and T. asperellum). However, there has been no studies regarding antitumoral molecules in the T. asperelloides extract. The aim of this project was to evaluate the biological effects of the etanolic extract of the T. asperelloides (ExtTa) fungus and its fractions on human (MDA-MB-231 and MCF7) and mouse (4T-1) breast tumor cell lineages. The hyphae and spore extract was made with 95% ethanol and the fractions were separated by FPLC. Using BCA (bicinchoninic acid) and DNS (dinitrosalisilic acid) 40,00 mg/ml and 139,07 mg/ml of protein and 7,08 mg/ml and 10,20 mg/ml of carbohydrates were isolated in ExtTa 1 and 2 respectively. SDS-Page of the protein showed that most of the proteins presented a mass between 30 and 3,5 kDa and the Schiff staining showed predominance of glycoproteins. Cellular viability MTT assay showed that the extracts had high toxicity to tumor cells. The non-tumor human fibroblast lineage GM637 was used to determine the selectivity index (SI) and MDA-MB-231 was the most susceptible cell line. Fractions 4.1 and 5.2 showed a higher IS (1,96 and 1,92 respectively). The influence of ExtTa on the oxidative stress was measured using a DFCH-DA probe, which showed no influence over the production of ROS. Also, flow cytometry showed that the ExtTa seems to induce G0-G1 cell cycle arrest and reduction of the number of MDA-MB-23 cells in S phase. An increase on the number of autophagic vesicles in both MDA-MB-231 and GM637 lineages was observed through ETM (electronic transmission microscopy), after the treatment with ExtTa. These results suggest that the T.asperelloides has a cytotoxic potential against tumor cells and biological effects on cycle cell arrest and autophagy vesicle formation on the adenocarcinoma MDA-MB-231.